PROSES BERPIKIR DIVERGEN MATEMATIS PESERTA DIDIK DALAM MENYELESAIKAN SOAL OPEN ENDED DITINJAU DARI HABITS OF MIND - Muhammad Arif Nasrulloh; Supratman Supratman; Diar Veni Rahayu (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2022)
The purpose of this study was to describe the mathematical divergent thinking process of students in solving open-ended questions in terms of habits of mind. The research conducted is a qualitative research with exploratory methods used. The research subjects consisted of six students in the eighth grade of junior high school. The research was analyzed based on the aspects of fluency, flexibility, originality and elaboration. The results showed that: 1) Students with good habits of mind are able to carry out the work process according to the previous strategy skillfully, are able to have thoughts about something different, are able to generate ideas and ideas to design a settlement strategy without requiring a long time and are able to design and using a solution strategy with the right mathematical concepts without requiring a long time. 2) Students with moderate habits of mind are able to carry out the work process according to the previous strategy even though it still needs to be developed again, able to have thoughts about something different even though it still needs to be developed again and there are still mistakes, able to generate ideas and ideas for designing a solution strategy by re-identifying the problem repeatedly and being able to come up with a strategic plan that will be used by re-identifying the previously studied problems. 3) Students with poor habits of mind are able to carry out the work process according to the previous strategy even though there are still errors, able to have thoughts about something different even though there are still errors, able to generate ideas and ideas to design a settlement strategy by identifying return to the problem even though there are still errors in calculations and require repetition in understanding and recalling relevant material to plan problem solving strategies. Keywords: Mathematical Divergent Thinking Process, Open Ended, Habits of Mind